The Analysis of Communication Climate and Organizational Culture for Increasing the Performance of Regional Development Planning - Erwin Pardede (Indonesian Journal of Geography, 2014)
One of the attempts to improve the quality of human resources in a certain area is to utilize the role of theIndustrial Training and Education Center Regional I of the Ministry of Industry, Medan. In order to maximize the performanceof planning in the Industrial Training and Education Center Regional I of the Ministry of Industry, Medan,we need to know what factors which should be considered in its achievement.For this reason, there is the problem of theresearch as follows: how about the influence of the Climate of Organizational Culture and Communication in improvingthe performance of Regional Development Planning at the Industrial Training and Education Center Regional I ofthe Ministry f Industry, Medan. The objective of the research was to analyze the correlation between communicationclimate and organizational culture in order to improve the performance of Regional Development Planning Regional Iof the Ministry of Industry, Medan.The research used explanatory quantitative approach. The samples consisted of 267respondents. The data were analyzed by using descriptive statistic analysis and inferential statistic analysis with SEMequation model and processed by using an Amos version 16 software program.The result of the research showed thatcommunication climate and organizational Culture play a very important role for improving the planning performanceof in its implementation.